Amide proton transfer imaging of high intensity focused ultrasound‐treated tumor tissue. Issue 4 (23rd October 2013) - Hectors, Stefanie J.C.G.; Jacobs, Igor; Strijkers, Gustav J.; Nicolay, Klaas
<x xml:space="preserve">Abstract</x> Purpose In this study, the suitability of amide proton transfer (APT) imaging as a biomarker for the characterization of high intensity focused ultrasound (HIFU)‐treated tumor tissue was assessed. Methods APT imaging was performed on tumor‐bearing mice before (n = 15), directly after (n = 15) and at 3 days (n = 8) after HIFU treatment. A control group (n = 7) of nontreated animals was scanned at the same time points. Histogram analysis of the tumor APT‐weighted signal distributions was performed to assess HIFU‐induced changes in the tumor APT contrast. Results Distinct regions of decreased APT‐weighted signal were observed at both time points after HIFU treatment. Analysis of the tumor APT‐weighted signal distribution showed a pronounced shift toward lower APT‐weighted signal values after HIFU treatment. A significantly increased fraction of pixels with an APT‐weighted signal value between −10 and −2% was observed both directly (0.37 ± 0.16) and at 3 days (0.49 ± 0.16) after HIFU treatment as compared to baseline (0.22 ± 0.16). Conclusion The presented results show that APT imaging is sensitive to HIFU‐induced changes in tumor tissue and may thus serve as a new biomarker for monitoring the response of tumor tissue to HIFU treatment. Magn Reson Med 72:1113–1122, 2014. © 2013 Wiley Periodicals, Inc.